Learnings about design from recycling by using post-consumer polypropylene as a core layer in a co-injection molded sandwich structure product. (April 2021) - Gall, Markus; Steinbichler, Georg; Lang, Reinhold W.
Abstract: In pursuit of a circular economy of plastics, there is a need to use more recycled plastics for new products. Polypropylene (PP) constitutes a major fraction of post-consumer plastic wastes, and mechanical recycling is currently the most sustainable recovery strategy. Sandwich-structured multi-layer products with recyclate cores are a seemingly easy way to satisfy demands for recyclate utilization without compromising on product aesthetics. We present the case of a reusable plastic transport box with a recycled content of 45 wt% manufactured by a co-injection molding process. The box was characterized by spectroscopic and thermo-analytical methods. Mechanical performance was tested on both specimen and product levels. A comparison was made to transport boxes fabricated entirely from virgin or entirely from recycled PP, respectively. A number of contaminants including foreign polymers were identified within the recyclate core layer of the sandwich-structured material. While these contaminants had no deteriorative effect on stiffness-controlled performance, a strong influence on strength-controlled and impact-related properties was observed. We argue that the presence of inclusions of both polymeric and inorganic nature is an intrinsic quality characteristic of post-consumer recyclates. These need to be considered in any design-from-recycling philosophy to guarantee functionality, reliability, and safety of products with recycled content. Graphical abstract: Unlabelled Image Highlights: Plastic crates with sandwich-structured multi-layer walls comprising a post-consumer recyclate core were made. Compositional analysis revealed foreign polymer contamination within the recyclate core resulting in incompatible inclusions. Despite contamination issues, incorporation of recycled content may improve short-term mechanical product performance. Defects in the recyclate core control impact performance of the entire sandwich structure regardless of tough skin layers. Design-from-recycling is discussed in the context of co-injection molded sandwich structures.